Pengaruh E-Service Quality dan E-Promotion Terhadap Keputusan Pembelian Pada Pelanggan Rumah Makan Meyfood di Purwakarta - Ninda Meidiani; Danang Kusnanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study has the aim of knowing, analyzing and explaining the phenomenon of the effect of e-service quality and e-promotion on purchasing decisions for Meyfood restaurant customers in Purwakarta. This research is a descriptive quantitative approach. Sampling in this study used incidental sampling with 170 samples of respondents, namely customers of Meyfood restaurants in Purwakarta. In this study, the validity of the data and the classical assumption test were carried out. Scale Range Analysis and Path Analysis Techniques with the help of the Method of Successive Interval (MSI), Microsoft Excel 2010 program and SPSS version 25 were used as data analysis techniques in this study. The results showed that E-Service Quality and E-Promotion have a strong relationship. As well as E-Service Quality and E-Promotion have a positive and significant effect on Purchase Decision.